The Influence Of Transparency And Accountability On The Level Of Satisfaction Of Muzakki BAZNAS, Musi Banyuasin District - Helisia Krisdayanti; Mismiwati Mismiwati; Khoiron Pratama; Fakhrina Fakhrina; Riduwansah Riduwansah (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2023)
This research was conducted to increase service satisfaction for muzakki at BAZNAS Kab. Musi Banyuasin must report all activities, including management reports, performance reports and financial reports on a monthly, semester (six month) and annual scale, which are reported at the right time and in a fast and precise manner. This research aims to determine the influence of Transparency and Accountability on the Satisfaction Level of Muzakki Baznas Musi Banyuasin Regency. This research uses primary data obtained from distributing questionnaires using a Likert scale. The sampling technique in this research used a nonprobability sampling method. The number of samples obtained was 96 Muzzaki samples at BAZNAS Kab. Musi Banyuasin. Based on the results of research conducted by researchers, it can be concluded that: Transparency has no effect on the level of satisfaction of BAZNAS muzakki in Musi Banyuasin Regency. This is shown by the results of the T test which has a Tcount value of 1.088, smaller than the Ttable value of 1.660. Accountability has no effect on the level of satisfaction of BAZNAS muzakki in Musi Banyuasin Regency. This is shown by the results of the T test which has a Tcount value of 1.655 which is smaller than the Ttable value of 1.660.